(untitled) (Asian Education Studies, 2022)
Vigorously developing vocational education has become one of Chinese basic national policies. In the era of "Internet Plus", vocational education is also changing rapidly. Vocational education has the dual attributes of education and industry. The new era requires a deeper integration of vocational education with the Internet, which is a great challenge for vocational schools. Based on the background of the current "Internet Plus" era, this paper clarifies the necessity of the innovation of vocational education management model, and proposes strategies for the diversified development and innovation of this mode, aiming to better realize a deep integration of vocational education with the Internet.